PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL NUMBERED HEADS TOGETHER UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII SMP NEGERI 03 ROKAN IV KOTO - Satria Putra Purba; Titi Solfitri; Zulkarnain ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to improve the learning process and improve students' mathematics learning outcomes through the implementation of cooperative learning with Numbered Heads Together structural approach. This type of research is Classroom Action Research with two cycles. The research was conducted in class VIII SMP Negeri 03 Rokan IV Koto in second semester of the 2015/2016 academic year with the subject of 34 students. The research instrument consists of learning tools and instruments to collect data. This study used syllabus, lesson plans and worksheets. Data collection instruments used in this study is the observation sheet and students’ test. Data analysis technique used are analysis descriptive narrative of qualitative data and descriptive statistical analysis of quantitative data. Based on the results of the study, the learning process has improved and students' mathematics learning outcomes also increased after applying cooperative learning with Numbered Heads Together structural approach. Thus, cooperative learning with Numbered Heads Together structural approach can be implemented as an alternative to learning, because learning approaches can improve the learning process and improve student learning outcomes.Keywords: Cooperative Learning, Structural Approach Numbered Heads togheter, Learning Process, Learning Outcomes.